(3JMaI Chdj GdCdHGH aj UfGYI GdNW hGdcJGHs - (3YHO GdQMef Hf jhSa, GHf GdUGFZ,J (B845 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj Yde HGdbde Yde GdEfSGf eG de jYde s
(3BNQgG (B:s
(3ef Gdfhf hGdOGd EPG cGf eaQOkG CVjb ef GdeQcHI hGddg SHMGfI hJYGdi CYde s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3UfGYI (B14) s
Keywords: (3GdNW hCdGJgs